Topical 0.05% clobetasol propionate versus 1% pimecrolimus ointment in vitiligo - Coskun, B; Saral, Y; Turgut, D (Jle, 2005)
Vitilicyo is a common skin condition resulting from loss of normal melanin pigments in the skin which produces white patches. Topical corticosteroids are indicated for the treatment of limited areas of vitiligo. Pimecrolimus, which inhibits calcineurin, has recently been shown to be effective for the treatment of vitiligo. We performed a prospective study to evaluate the efficacy of the 0.05% clobetasol propionate and 1% pimecrolimus in the treatment of vitiligo. Ten patients with virtually bilateral symmetrical lesions of vitiligo were included. 0.05% clobetasol propionate was applied twice daily over the lesion on right side of the body, and topical 1% pimecrolimus was applied twice daily over the lesion on left side of the body. It was determined that both treatment modalities resulted in a comparable rate of repigmentation. Response to treatment was varied according to the anatomical location of the lesions where better results were seen on the trunk and extremities. Results from this pilot study indicate that topical 1% pimecrolimus is as effective as clobetasol propionate in restoring skin disfiguring due to vitiligo. For a better conclusive statement further studies involving larger groups of patients should be performed.
Keywords: clobetasol proprionate; pimecrolimus; vitiligo